Jarosite and Alunite in Ancient Terrestrial Sedimentary Rocks: Reinterpreting Martian Depositional and Diagenetic Environmental Conditions - Sally L. Potter-McIntyre; Thomas M. McCollom (Life, 2018)
Members of the alunite group are precipitated at low pH (<1 to ~4) in oxidizing environments, are unstable in circumneutral conditions, and are widespread on Mars. At Mollies Nipple in Kane County, Utah, USA, jarosite and alunite are abundant as diagenetic cements in Jurassic sandstones. This research characterizes the jarosite and alunite cements with the goal of determining their origin, and tests the hypothesis that jarosite and alunite may be more stable than the current understanding indicates is possible. Previous studies have placed the jarosite- and alunite-bearing caprock at Mollies Nipple in the Navajo Sandstone, but the presence of water-lain deposits, volcanic ash, volcanic clasts, and peloids show that it is one of the overlying Middle Jurassic units that records sea level transgressions and regressions. A paragenetic timing, established from petrographic methods, shows that much of the cement was precipitated early in a marginal marine to coastal dune depositional environment with a fluctuating groundwater table that drove ferrolysis and evolved the groundwater to a low pH. Microbial interaction was likely a large contributor to the evolution of this acidity. Jarosite and alunite are clearly more stable in natural environments than is predicted by laboratory experiments, and therefore, the Martian environments that have been interpreted as largely acidic and/or dry over geologic time may have been more habitable than previously thought.